Connection of Quasi-Resonant Amplification to the Delay in Atmospheric Residence Times Over India - Lakshmi Kumar, T. V.; Durga, G. Purna; Rao, K. Koteswara; Barbosa, Humberto; Kulkarni, Ashwini; Patwardhan, Savita; Mall, R. K.; Rao, V. Brahmananda (Frontiers in Earth Science, 2021)
Mean monthly Atmospheric Residence Times (ART), deduced from the global climate models of Coupled Model Intercomparison Project 5 (CMIP5) under RCP4.5 and RCP8.5 emission scenarios over Indian landmass, show a perceptible increase by the end of the 21st century. India, being a tropical country, faces prolonged ART, particularly during the June month of Southwest monsoon season (June to September) which will be an indicative measure of the increased frequency of extreme weather events. Here we show a possible connection of quasi-resonant amplification (QRA) to the recent (August 2018) Kerala heavy rains that resulted in severe floods and claimed more than 400 mortalities. Remarkable delay in residence times over India during June is shown to have an association with QRA evidenced by the higher magnitudes of amplitudes at the wavenumbers 6 and 7 from the 19 global climate models of CMIP5 under the RCP4.5 and RCP8.5 scenarios.